2021
DOI: 10.1021/acs.macromol.0c02305
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Theoretical and Experimental Study of the Polymer Matrix-Mediated Stress Transfer in a Cellulose Nanocomposite

Abstract: We study composites of cellulose nanocrystals (CNCs) in an ionomer matrix of poly(ethylene-stat-sodium acrylate) and find that direct cellulose/cellulose interactions in the composite are not a requirement for achieving reinforcement. While isotropic composites only show a slightly enhanced stiffness compared to the neat ionomer, a more substantial increase in Young's modulus by a factor of up to 5 is achieved by uniaxial alignment of the composites through melt spinning. The orientation of CNC in melt-spun co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The presence of polar acrylic acid groups on the EAA7 chains make the polymer relatively more hydrophilic and thus improve the EAA7-CNC compatibility. 10,18 The poorer adhesion between PCL and CNC is also reflected in the higher surface roughness of the PCL-based composites.…”
Section: Visual Appearance and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of polar acrylic acid groups on the EAA7 chains make the polymer relatively more hydrophilic and thus improve the EAA7-CNC compatibility. 10,18 The poorer adhesion between PCL and CNC is also reflected in the higher surface roughness of the PCL-based composites.…”
Section: Visual Appearance and Morphologymentioning
confidence: 99%
“…Poly(ethylene-co-acrylic acid) (EAA) is a copolymer commonly used in the packaging industry, containing acrylic acid groups, providing good adhesion with a hydrophilic reinforcement. 10,[16][17][18] As biodegradable alternative to EAA, poly(ε-caprolactone) (PCL) was selected considering its biodegradability, high ductility, and toughness, but with a relatively more hydrophobic surface than the EAA. 19 Both matrices have relatively low melting points thus enabling more effective water-assisted extrusion and the possibility of low processing temperatures, which are beneficial to prevent cellulose degradation.…”
Section: Introductionmentioning
confidence: 99%
“…When the PTFE addition was 0.5%, the maximum value of φ was 0.98, which was very close to 1, indicating that 0.5#MCC and PBAT had very high interfacial adhesion strength, which was consistent with the results observed by SEM and mechanical performance. Thus, it can be concluded that strong cellulose/polymer interaction is conducive to stress transfer and enhance mechanical properties [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Machine Learning. (1) The dimensionality reduction model based on the GCN + a + g and MLP was implemented using Python and the TensorFlow framework. 67 This model was trained with a learning rate of 0.001 and a decay of 0.95 using a minibatch size of 50 and the Adam optimizer.…”
Section: ■ Methodsmentioning
confidence: 99%